THE PIGMENT IMPACT ON RHEOLOGICAL PROPERTIES OF ANTICORROSION PROTECTION COVERS OF MANUFACTURED RAILWAY TRANSPORT CONSTRUCTIONS - Plugin, A. N.; Trikoz, L. V.; Gerasimenko, O. S.; Podtelezhnikova, I. V. (Science and Transport Progress, 2010)
In the article the influence of the electro-surface potential value on change of the suspension viscosity values of pigments was investigated. It was done for pigments different in chemical nature – titanium oxide and ferric oxide. It was demonstrated that at equal dispersed phase concentrations the higher viscosity value was shown by systems with pigment TiO2 and the lower one – with Fe2O3. This fact correlates well with the absolute values of electrosurface potentials of the pigments studied. The active centers of the particles produce structuring effect on the dispersed medium molecules thus increasing the system viscosity.